Cataract Surgery with Primary Lens Implantation in Children with Chronic Uveitis. (17th February 2018) - Guindolet, Damien; Dureau, Pascal; Terrada, Céline; Edelson, Catherine; Barjol, Amandine; Caputo, Georges; LeHoang, Phuc; Bodaghi, Bahram
ABSTRACT: Purpose : To evaluate the evolution of chronic uveitis in children undergoing cataract surgery with primary intraocular lens (IOL) implantation. Methods : Twelve children with chronic uveitis underwent cataract surgery with primary posterior chamber intraocular lens (IOL) implantation. Results : Fourteen eyes were implanted with a foldable hydrophobic acrylic IOL. The mean follow-up was 35.39 months (8.72–69.57). The mean BCDVA before surgery and at the end of follow-up was 1.11 (0.40–2.30; SD: 0.57) and 0.48 (0–3; SD: 0.77; p =0.007) respectively. The mean oral corticosteroids dosage after surgery and at the end of follow-up was 0.80 mg/kg/day (SD: 0.37) and 0.17 mg/kg/day (SD: 0.24; p =0.001) respectively. All patients except one were treated with methotrexate. Four patients (5 eyes) were additionally treated with anti-tumor necrosis factor agent. Conclusions : Cataract surgery with primary posterior chamber hydrophobic IOL implantation is possible and leads to a good visual recovery in cases of pediatric chronic uveitis. This surgery requires aggressive anti-inflammatory management with immunosuppressive drugs to control inflammation and reduce the corticosteroids dosage.